FACTORS CONTRIBUTING TO SUSCEPTIBILITY OF URINARY TRACT INFECTION AMONG PREGNANT WOMEN ATTENDING ANTENATAL AT ENTEBBE REGIONAL REFERRAL HOSPITAL WAKISO DISTRICT. A CROSS-SECTIONAL STUDY - Nassuuna, Bridget; Namubiru, Rebecca T; Nansereko, Hasifa; Naggulu, Immaculate Prosperia; Nalubega, Jane Frank (Student’s Journal of Health Research Africa, 2025)
Background The aim of the study is to determine the factors contributing to susceptibility of urinary tract infection among pregnant women attending antenatal at Entebbe regional referral hospital Wakiso district. Methodology The study employed a descriptive cross-sectional study design that used quantitative methods of data collection from 36 pregnant women who attended antenatal care at Entebbe Regional Referral Hospital. The study employed a simple random sampling technique to select the sample. The collected data were summarized on paper using a pen, tallied, analyzed using Microsoft Excel, and then presented in the form of tables, pie charts, and graphs. Results The majority, 30 (83.3%), of the respondents were married, and the least, 6 (16.7%), were single. Most, 25 (69.4%) of the respondents reported having one sexual partner, Most, 23 (63.9%) of the respondents did not change their undergarments, most, 20 (55.6%) of the respondents said Yes when asked whether they had ever had about UTI, majority, 31 (86.1%) shared toilets with their neighbors, 18 (50%) bathed twice in a day, 18 (50%) of the respondents urinated four times and above, majority, 23 (63.9%) of the respondents had no history of any chronic illness. Most, 12 (33.3%) of the respondents were attending their fourth antenatal visit. The Majority, 25 (69.4%) of the respondents had never inserted a catheter. Most of the respondents, 21 (58.3%), were multigravida mothers. Conclusions The susceptibility of urinary tract infections among pregnant women in Entebbe was 20.3% and was associated with Occupation, marital status, gravidity, and education level. Recommendations Ministry of health and other responsible bodies including the health workers should strive to increase the knowledge of patients about the importance of reporting and obtaining medical consultation.